ANALISIS PELAKSANAAN PERAN GENDER PADA ANGGOTA PUNGUAN BORSAK MANGATASI NABABAN DI KOTA PONTIANAK - Nababan, Ribka Mariani; Okianna, Okianna; Prancisca, Stella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The aim of writing this thesis is to determine the implementation of "Gender Roles in Punguan Borsak Mangatasi Nababan in Pontianak City". There are several objectives in this research, namely to find out how; implementation of gender roles, namely in the public sector/productive activities, the domestic sector/reproductive activities, and the community sector/social activities. The research method used is a descriptive method in the form of qualitative research. Data collection techniques in this research are through interviews, observation and documentation, while the data collection tools used are observation guides, interview guides and documentation tools in the form of smartphones. The analysis in this research is presented in a qualitative descriptive manner using 2 pairs of informants. The research results show that (1) the implementation of gender roles in the public sector/productive activities is demonstrated by the existence of an agreement between husband and wife in earning a living, especially the husband as head of the family to give freedom to the wife in participating in earning a living to increase family income, (2) implementation of gender roles in the domestic sector/reproductive activities, shown by the cooperation between husband and wife in carrying out household tasks, (3) implementation of gender roles in the community sector/social activities shown by the attitude of husband and wife who still maintain mutual ties with each other. neighbors, and an enthusiastic attitude to participate in every series of events or activities held in certain groups or organizations that the husband and wife have participated in.